Promosi Penggunaan Selebriti Instagram (Selebgram) Dalam Meningkatkan Penjualan Astwear.Id Pada Generasi Milenial Di Kota Makassar - Yusryana, Yusryana; Majid , Abdul; Idris , Muhammad (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This type of research aims to be used is qualitative descriptive research. The primary and secondary data sources where primary data are data sources obtained directly using observation and interview methods, polls from individuals or a group while secondary are data sources obtained through media intermediaries or indirectly in the form of books. the methods used are observation, interview, and document methods. Based on the results of research on marketing communication strategies conducted by @Astwear.id consisting of product, price, place, promotion, people, process, packaging and payment. Through the promotion element @Astwear.id take advantage of Instagram features such as Follow, Post, Automatic Direct Massage, create creative content, apply give away, then do ads with using endorsement and paid promotion services.